The Influence of Overheating Temperature on the Shape Change of Primary Silicon Crystals and the Mechanical Properties of AlSi17 Alloy - K.K. Hillebrandt-Szymańska; J. Piątkowski (Archives of Foundry Engineering, 2025)
The article presents the concept of overheating the liquid AlSi17 alloy significantly above the Tliq. temperature, holding it at this temperature for a specified time, and casting it into two moulds with different cooling rates: a bentonite-based sand mould and a copper chill mould. Based on the obtained research results, it was found that overheating the AlSi17 alloy to temperatures of 920-960°C significantly improves mechanical properties, namely: tensile strength by approximately 40%, yield strength by approximately 70%, elongation by approximately 89% (for the sand mould - SM) and approximately 61% (for the copper metal mould - MM), reduction of area/ narrowness by approximately 67% (for SM) and approximately 51% (for MM) compared to the alloy without overheating. This process also reduces the scatter of the tested properties, indicating better homogeneity of the cast structure. Overheating the AlSi17 alloy to the optimal temperature range above Tliq. (in terms of the tested mechanical properties) also affects the morphology of primary silicon crystals. Such a structure, improving mechanical properties, increases the application area of hypereutectic Al-Si alloys, especially in the automotive and aerospace industries for heavily loaded castings operating under extreme thermal-mechanical stress conditions.